The stimulus response of chitosan and its depression effect on talc flotation. Issue 1 (2nd January 2018) - Feng, Bo; Peng, Jinxiu; Guo, Wei; Zhu, Xianwen; Huang, Wanfu
ABSTRACT: The depressant effect of chitosan on talc flotation has been studied and the results show that chitosan is a useful depressant for talc flotation and that its depression effect is independent of pH. However, the adsorption mechanisms are different at different pH values. In acidic solutions, chitosan behaves like a weakly charged polyelectrolyte, and electrostatic attraction is the main driving force for adsorption. In alkaline solutions, chitosan is less soluble and forms large aggregates, and adsorption is very great. The effect of a switch in solution pH on adsorbed chitosan layer was also investigated. The switch of pH from 9 to 3 results in an increased depression effect of chitosan and this change is reversible. The reason is that chitosan is positively charged and soluble in water at low pH. When the pH decreases, chitosan loses its hydration water. Upon pH induced dehydration, the polymer's hydrophilic groups are exposed, and this results in a distinct lowering of the recovery of the talc.